Check list of the Hydrophilidae (Coleoptera) species of Turkey and a new record for the Turkish fauna - Incekara, Ümit; Mart, Abdullah; Erman, Orhan (My University, 2003)
A check list of Hydrophilidae species known in Turkey is presented for the first time. In addition, their distributions in Turkey are given. Fifty-four species are determined. Of these, Hydrophilus atterimus Eschscholtz, 1822, a new record for the Turkish fauna, is reviewed and compared with H. piceus (Linnaeus, 1758).
Türkiye Hydrophilidae (Coleoptera) Türlerinin Listesi ve Türkiye Faunasi Için Bir Yeni Kayit
Keywords: Coleoptera; Hydrophilidae; New record; Systematics; Turkey